(untitled) (Nigerian Journal of Technology, 2016)
The optimal sizing and location of distributed generators (DG) remain crucial factors in their application for active power loss minimization as well as voltage profile improvement. This paper describes an analytical method for the optimal sizing and placement of DG in the Nigerian power network for active power loss minimization. The effectiveness of the proposed method showed a 6.2% reduction in active power losses on the 33kV Nigerian network (i.e. from 92.7MW to 87.0MW). The results showed an improvement in the voltage profile of that six load buses whose voltages were outside the statutory limit of 0.95 pu? Vi ? 1.05pu.